Excess endocrine growth hormone in acromegaly promotes the aggressiveness and metastasis of triple-negative breast cancer - Chan Woo Kang; Ju Hun Oh; Eun Kyung Wang; Yaru Bao; Ye Bin Kim; Min-Ho Lee; Yang Jong Lee; Young Seok Jo; Cheol Ryong Ku; Eun Jig Lee (iScience, 2024)
Summary: Pituitary adenoma-induced excess endocrine growth hormone (GH) secretion can lead to breast cancer development and metastasis. Herein, we used an acromegaly mouse model to investigate the role of excess endocrine GH on triple-negative breast cancer (TNBC) growth and metastasis. Additionally, we aimed to elucidate the molecular mechanism of transcription factor 20 (TCF20)/nuclear factor erythroid 2-related factor 2 (NRF2) signaling-mediated aggressiveness and metastasis of TNBC. Excess endocrine GH induced TCF20 activates the transcription of NRF2 and NRF2-target genes to facilitate TNBC metastasis. Inhibition of GH receptor (GHR) and TCF20 activity using the GHR antagonist or small-interfering RNA-induced gene knockdown resulted in reduced tumor volume and metastasis, suggesting that excess endocrine GH stimulates TCF20/NRF2 pathways in TNBC and promotes metastasis to the lung. GHR inhibitors present an effective therapeutic strategy to prevent TNBC cell growth and metastasis. Our findings revealed functional and mechanistic roles of the GH-TCF20-NRF2 signaling axis in TBNC progression.